Environmentally and Socially Oriented Investments on Sustainable Development of Rural Areas - ARANCHIY, Valentyna; ZORIA, Oleksii; YASNOLOB, Ilona; ZORYA, Svitlana; GORB, Oleg; MYKOLENKO, fInna; DYVNYCH, Olha; CHUMAK, Valentyna; BRAZHNYK, Liudmyla (Journal of Environmental Management and Tourism; Vol 12 No 2 (2021): JEMT Volume XII Issue 2(50) Spring 2021DO - 10.14505//jemt.v12.2(50).02, 2021)
Theoretical, methodological, scientific, methodical and applied principles of managing environmentally and socially oriented investments in sustainable development of rural areas have been developed and substantiated in the article. The model of investment process of ecologically and socially oriented economy has been developed. The analysis of corresponding existing models of investment process enabled to specify the management model, which corresponds to the environmentally and socially oriented economics. The block scheme of the system of analyzing and evaluating the efficiency of investment processes of sustainable rural development has been made. The determined methodological provisions and specified concepts enabled to ground the system of complex analyzing and assessing the effectiveness of investment processes in sustainable development of rural areas, including the evaluation of economic, social and environmental efficiency of investment projects. The mechanism of sustainable rural development, comprising consolidated elements and connections, has been grounded. The ecological aspects of investment policy as a component of the economic mechanism of sustainable rural development have been systematized. It has been determined that attracting investments in environmentally and socially oriented investment projects and programs has to be based on strengthening the ecological aspects of investment policy as part of stimulating sub-system of the economic mechanism of sustainable rural development.